Physical Theory and its Interpretation Essays in Honor of Jeffrey Bub - Demopoulos, William; Pitowsky, Itamar (The Western Ontario Series in Philosophy of Science, A Series of Books in Philosophy of Science, Methodology, Epistemology, Logic, History of Science, and Related Fields, 2006)
The essays in this volume were written by leading researchers on classical mechanics, statistical mechanics, quantum theory and relativity. The papers cover a number of central topics in the foundations of physics, including the role of symmetry principles in classical and quantum physics (papers by Butterfield and by Healey), Einstein's hole argument in general relativity (Korte), quantum mechanics and special relativity (Hemmo and Berkovitz, Brown and Timpson), quantum correlations (Glymour, Redei), quantum logic (Demopoulos, Isham, Stairs), and quantum probability and information (Gudder, Pitowsky). The authors - philosophers, physicists, and mathematicians - represent a broad spectrum of approaches to foundational issues at the frontiersof contemporary research. This befits a volume in honor of Jeffrey Bub, one of the leading philosophers of physics of the last thirty years, whose influence on the field is evident all the essays collected for this volume.